Nucleon-Nucleon Potentials and Computation of Scattering Phase Shifts - Jhasaketan Bhoi; Ujjwal Laha (Department of Physics, Sebelas Maret University, 2015)
By judicious exploitation of supersymmetry formalism of quantum mechanics higher partial wave nucleon-nucleon potentials are generated from its ground state interactions. The nuclear Hulthen potential and the corresponding ground state wave function with the parameters of Arnold and MacKellar are used as the starting point of our calculation. We compute the scattering phase shifts for our constructed potentials through Phase Function Method to examine the merit of our approach to the problem.